Surface-engineered smart nanocarrier-based inhalation formulations for targeted lung cancer chemotherapy: a review of current practices - Xian-Yan Yu; Xue Jin; Zhang-Xuan Shou (Taylor & Francis Group, 2021)
Lung cancer is the second most common and lethal cancer in the world. Chemotherapy is the preferred treatment modality for lung cancer and prolongs patient survival by effective controlling of tumor growth. However, owing to the nonspecific delivery of anticancer drugs, systemic chemotherapy has limited clinical efficacy and significant systemic adverse effects. Inhalation routes, on the other hand, allow for direct delivery of drugs to the lungs in high local concentrations, enhancing their anti-tumor activity with minimum side effects. Preliminary research studies have shown that inhaled chemotherapy may be tolerated with manageable adverse effects such as bronchospasm and cough. Enhancing the anticancer drugs deposition in tumor cells and limiting their distribution to other healthy cells will therefore increase their clinical efficacy and decrease their local and systemic toxicities. Because of the controlled release and localization of tumors, nanoparticle formulations are a viable option for the delivery of chemotherapeutics to lung cancers via inhalation. The respiratory tract physiology and lung clearance mechanisms are the key barriers to the effective deposition and preservation of inhaled nanoparticle formulations in the lungs. Designing and creating smart nanoformulations to optimize lung deposition, minimize pulmonary clearance, and improve cancerous tissue targeting have been the subject of recent research studies. This review focuses on recent examples of work in this area, along with the opportunities and challenges for the pulmonary delivery of smart nanoformulations to treat lung cancers.